2010
DOI: 10.1089/tmj.2009.0132
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Integrated Services Digital Network–Internet Protocol Solution for Resident Education

Abstract: The teaching efficacy of multipoint VTC is perceived by medical residents to be more effective when complemented by application-sharing software such as Adobe Acrobat Connect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Although this is the first report of virtual MOE in RO, it is not unique in its effort to successfully implement the latest technology to bridge gaps in RO education, with multiple successful international RO education initiatives dating back to 2007. 10 , 11 , 12 Additionally, a small randomized trial of in-person versus virtual MOEs for emergency medicine residents found no differences between the groups with respect to competency evaluation and quality of assessment. 13 This study also found that the examinees preferred the virtual format and found it to be less intimidating.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although this is the first report of virtual MOE in RO, it is not unique in its effort to successfully implement the latest technology to bridge gaps in RO education, with multiple successful international RO education initiatives dating back to 2007. 10 , 11 , 12 Additionally, a small randomized trial of in-person versus virtual MOEs for emergency medicine residents found no differences between the groups with respect to competency evaluation and quality of assessment. 13 This study also found that the examinees preferred the virtual format and found it to be less intimidating.…”
Section: Discussionmentioning
confidence: 98%
“…Although this is the first report of virtual MOE in RO, it is not unique in its effort to successfully implement the latest technology to bridge gaps in RO education, with multiple successful international RO education initiatives dating back to 2007. [10][11][12] Additionally, a small Examiner On Screen…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] Although the cost of the hardware may present a budgetary challenge for smaller clinics, 33 the approach we propose will naturally scale upward as network capacities are expanding, giving users the ability to see and hear in high definition, while engaging in the real-time remote manipulation of complex treatment plans. The solution also gives users the ability to seamlessly interact, as if working side by side.…”
Section: Discussionmentioning
confidence: 99%
“…These applications can enhance dissemination of SBT and globalization of training efficiently, leading to standardization of patient care [124]. Distributed simulation can be enhanced by integrating application sharing software into simulations [125]. Having learners utilize GHS-related desktop or mobile applications that are demonstrated and screen-shared by remote facilitators can reinforce their use.…”
Section: Distributed Telesimulationmentioning
confidence: 99%